Joint DOAs-Timings Estimation for Uplink DS/CDMA Communication System Based on Esprit-Music Algorithm - WEI-CHIANG, WU (Engineering Transactions, 2005)
This paper proposes a blind algorithm to jointly estimate the direction-of-arrivals (DOAs) and timings (time-delays) in asynchronous DS/CDMA multiuser communication system. Making use of the space-time characteristics of an antenna-array DS/CDMA model, it is shown that the multiple signal classification (MUSIC) algorithm and the estimation of signal parameters via rotational invariance (ESPRIT) technique that are widely used in array signal processing, can be applied to extract the direction-of-arrival (DOA) and timing information. Multiuser timing estimation is based on a MUSIC-like algorithm while ESPRIT is applied to estimate the DOA for each user. More specifically, the proposed algorithm is computationally efficient since it reduces the multiuser parameters’ estimation problem to a set of single-user’s parameter estimation problems. It requires only two eigen decomposition (EVD) and several (depending on the number of subscribers) one-dimensional searches. Computer simulations under different scenarios not only show the accuracy but also demonstrate that the proposed ESPRIT-MUSIC based DOA-timing estimator is near-far resistant.